Design and performance of a plastic optical fiber leakage sensor - Golnabi, H.; Azimi, P. (Optics and laser technology, 2007)
In this article design and operation of a plastic optical fiber (POF) sensor based on the unconventional light leakage from one fiber to another one causing intensity modulation are presented. The dominant loss mechanism was found to be the evanescent loss and based on this phenomenon the optical fiber sensor was designed. The penetration depth of evanescent wave as a function of different refractive index of cladding was calculated. Operation of this sensor was tested as a liquid level sensor for different liquids and the experimental results are compared. The dry (air interface layer) and wet output (liquid interface layer) signals for this probe were measured for a series of measurements and important factors concerning sensor operation are described. The precision of measured values, reproducibility of the results (1.35% error), and the stability of sensing operation as a function of time at different launching powers are also reported (0.85% error). The reported results for this design are promising and verify the successful operation of such a device as a liquid level probe and also as an on/off level switch.